2022
DOI: 10.1021/acsinfecdis.2c00184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Immunogenicity of a Methyl Rhamnan Pentasaccharide Conjugate from Pseudomonas aeruginosa A-Band Polysaccharide

Abstract: Pseudomonas aeruginosa was added to the World Health Organization’s priority pathogen list for research and development of new antibiotics in 2017. Alongside the development of new antibiotics to fight antimicrobial-resistant P. aeruginosa, vaccines would be an appealing addition to the toolbox health professionals have against this bacteria, which causes life-threatening respiratory infections. Recently, the structure of a novel immunogenic terminal carbohydrate moiety on the cell surface of P. aeruginosa was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…It was envisioned that instead, a p-tolyl thioglycoside could be first generated with the p-tolyl group as an anomeric protecting group throughout the synthesis as well as a glycosyl donor during late-stage glycosylation as previously implemented by others. 21,22 To start, acetylated D-mannose obtained as described previously 12 was converted to thioglycoside S2 in two steps with excellent yields by treatment with thiocresol under acidic conditions followed by acetate deprotection using Zempleń deacetylation. C6 deoxygenation was achieved, as previously reported, via the Appel reaction (S3), followed by reduction with palladium hydroxide to obtain D-rhamnose thioglycoside S4 in moderate yields (Scheme S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was envisioned that instead, a p-tolyl thioglycoside could be first generated with the p-tolyl group as an anomeric protecting group throughout the synthesis as well as a glycosyl donor during late-stage glycosylation as previously implemented by others. 21,22 To start, acetylated D-mannose obtained as described previously 12 was converted to thioglycoside S2 in two steps with excellent yields by treatment with thiocresol under acidic conditions followed by acetate deprotection using Zempleń deacetylation. C6 deoxygenation was achieved, as previously reported, via the Appel reaction (S3), followed by reduction with palladium hydroxide to obtain D-rhamnose thioglycoside S4 in moderate yields (Scheme S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…12 The resulting conjugates elicited good IgM and IgGspecific responses in mice. 12 Despite the encouraging results obtained from this original work, we strived to improve our conjugates to increase their immunogenicity. At first, we aimed to achieve the conjugation of the mimics to cross-reactive material 197 (CRM 197 ), as opposed to HSA, as CRM 197 is widely used in the clinic and is generally regarded as a safe and effective carrier protein.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Jamshidi et al reported on the successful development of a pentasaccharide conjugate from P. aeruginosa’s A-Band polysaccharide ( Figure 4 ). Evaluation of the immunogenicity showed that antibodies were able to recognize P. aeruginosa LPS [ 145 ]. Hegerle et al investigated a dual-use conjugate vaccine targeting both P. aeruginosa (rFlaA and rFlaB, carrier protein) and K. pneumoniae (O-polysaccharide O1, O2, O3 and O5, antigens).…”
Section: Conjugate Vaccine Antigensmentioning
confidence: 99%
“… ESKAPE pathogens and examples of target antigens: E. feacium : cell wall teichoic acid [ 141 ]; S. aureus : trisaccharide type 8 capsular polysaccharide [ 142 ]; K. pneumoniae : capsular polysaccharide K2 [ 143 ]; A. baumanii : pseudaminic-acid [ 144 ]; P. aeruginosa : methyl rhamnan pentasaccharide [ 145 ]; E. coli : serotype O25B [ 146 ]. …”
Section: Figurementioning
confidence: 99%